War : a primer for Christians - Allen, Joseph L., 1928- (Texas A & M University Press, 2014)
War: A Primer for Christians provides a concise introduction to the main approaches that Christians have taken toward war and examines each approach critically. Some Christians have supported their country's wars as crusades of good against evil. Others, as pacifists, have rejected participation in or support for any war. Still others have followed the just-war tradition in holding that it can be justifiable under some conditions to resort to war, but that then Christian love must limit the conduct of war. In an updated preface and new afterword, Allen explores aspects of current internationa.